A quantitative study on three-dimensional pore parameters and physical properties of sodic soils restored by FGD gypsum and leaching water. (15th October 2019) - Liao, Renkuan; Yu, Haoliang; Lin, Henry; Yang, Peiling
Abstract: The application of flue gas desulfurization (FGD) gypsum has been recognized as a feasible measure in enhancing the quality of sodic soils. Quantitative evaluation of the effects of FGD gypsum on three-dimension (3D) pore characteristics is beneficial for understanding the reclamation mechanism of FGD gypsum on sodic soils. We collected intact soil cores from a sodic field at four depths (0–10, 10–20, 20–40, and 40–60 cm) in northern China to reconstruct 3D pore structures using X-ray computed tomography (CT), thus quantifying the effects of FGD gypsum (10.1 and 14.5 t hm −2 ) and leaching water (1520 and 2200 t hm −2 ) on the 3D pore characteristics and related soil physical properties. The treatments using FGD gypsum with leaching water promoted the formation of new pores and significantly ( p < 0.05) increased the 3D image-based macroporosity, mesoporosity, total pore length, and number of nodes at depths of 0–20 cm, improving the permeability of sodic soils investigated, which is validated by the enhanced saturated hydraulic conductivity ( K sat ). Irrigation water of 1520 t hm −2 is demonstrated effective in assisting FGD gypsum dissolution and leaching, but excessive leaching water (2200 t hm −2 ) may reduce the permeability of 20–40 cm depth. The combined application of 14.5 t hm −2 FGD gypsum and 1520 t hm −2 leaching water is suggested to obtain the optimal result for the investigated sodic soils. This study offers an applicable strategy for sodic soils reclamation and provides a reference for revealing the improvement mechanism of sodic soils by FGD gypsum and leaching water. Highlights: The 3D pore characteristics of sodic soil reclaimed by flue gas desulfurization (FGD) gypsum were quantified. The soil Ksat can be estimated by 3D image-based total porosity, macroporosity, total pore length density, and node density. An amount of 14.5 t·hm-2 FGD gypsum with 1520 t·hm-2 leaching water was suggested for the investigated sodic soil.